2007
DOI: 10.1029/2006je002862
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of gypsum in the Mars north polar region

Abstract: [1] We describe the distribution and concentration of the largest Martian gypsum deposit discovered to date by the Mars Express OMEGA (Observatoire pour le Mineralogie, l'Eau, les Glaces et l'Activité) imaging spectrometer, its relationship to the late Amazonian-aged north polar dunes in which it is found, and its likely origin. Gypsum has not been discovered anywhere within the north polar region outside of the Olympia Undae dune sea. In the areas of highest gypsum a concentration, 35% pure gypsum grains of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 69 publications
3
116
1
Order By: Relevance
“…Fishbaugh et al (2007) postulated the gypsum formed by water sourced from nearby channels percolating through the dunes, while Masse et al (2011) suggested the gypsum crystals were originally present within the interior of the North Polar Cap and have collected as ablation tills by ice sublimation and then subsequently been reworked by winds. Masse et al (2011) proposed the gypsum crystals within the polar car formed by weathering of dust particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishbaugh et al (2007) postulated the gypsum formed by water sourced from nearby channels percolating through the dunes, while Masse et al (2011) suggested the gypsum crystals were originally present within the interior of the North Polar Cap and have collected as ablation tills by ice sublimation and then subsequently been reworked by winds. Masse et al (2011) proposed the gypsum crystals within the polar car formed by weathering of dust particles.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital detections of gypsum have been studied in the north polar sand dunes on Mars using OMEGA (Langevin et al, 2005;Fishbaugh et al, 2007) and CRISM data (Masse et al, 2011). Fishbaugh et al (2007) postulated the gypsum formed by water sourced from nearby channels percolating through the dunes, while Masse et al (2011) suggested the gypsum crystals were originally present within the interior of the North Polar Cap and have collected as ablation tills by ice sublimation and then subsequently been reworked by winds.…”
Section: Discussionmentioning
confidence: 99%
“…The basaltic North Polar dunes in the Olympia Undae are enriched with hydrated minerals (most likely gypsum, Langevin et al, 2005;Fishbaugh et al, 2007;Horgan et al, 2009), in contrast to the mafic composition inferred for other dark dunes on Mars (e.g., Rogers and Christensen, 2003;Ruff and Christensen, 2007;Tirsch et al, 2011). Recent mapping efforts using Observatoire pour la Mineralogie, l'Eau, les Glaces et l'Activité (OMEGA) and Compact Reconnaissance Imaging Spectrometer (CRISM) data show that hydrated minerals are concentrated in the large dark dunes of the circumpolar and adjacent dunefields, as well as in the dust deposited from out of the atmosphere that veneers the surface of the polar cap (Calvin et al, 2009;Horgan et al, 2009;Massé et al, 2010Massé et al, , 2012.…”
Section: Sediment Composition On Marsmentioning
confidence: 99%
“…The abundance and distribution of water on the martian surface throughout its history has also been inferred from the mapping of phyllosilicates Poulet et al, 2005Poulet et al, , 2008aPoulet et al, , 2008bLoizeau et al, 2007;Bishop et al, 2008;Combe et al, 2008;Ehlmann et al, 2008aEhlmann et al, , 2009Mustard et al, 2008;Marzo et al, 2009;Wray et al, 2009aWray et al, , 2009bCarter et al, 2010;Fairén et al, 2010); serpentines (Ehlmann et al, 2010); opaline silica-rich deposits (Bandfield, 2008;Milliken et al, 2008;Squyres et al, 2008;Rice et al, 2010), such as the recent discovery of extensive hydrated and poorly crystalline silica materials in the western Hellas Basin (Bandfield et al, 2013); carbonates (Ehlmann et al, 2008b;Boynton et al, 2009;Michalski and Niles, 2010;Morris et al, 2010); and other minerals characteristic of evaporites, such as sulfates Langevin et al, 2005;Fishbaugh et al, 2007;Mangold et al, 2008). Clay minerals are found almost exclusively in Noachian and early Hesperian terrains and are exposed to our view due to cratering in ejecta or within gullies found on the interior slopes of the crater walls, and in some cases within the sediments of craters (Wray et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%